Оnthology of innovation and technological processes in high school (Pedagogy of Higher and Secondary Education, 2013)
Melnychuk I. М. Оnthology of innovation and technological processes in high school.The article reveals the essence of innovation and technological processes that take place in high school at the present stage of development of education. Scientific approaches to understanding the category of «educational technology» are generalized. Three fundamentally different technologic systems of the educational process that appear in scientific and educational research nowadays are structured.
Keywords: innovation; educational technology; innovation and technological processes; technologic systems of the educational process